Analisis Akad Mudharabah di Perbankan Syariah - Hidayati Nasrah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
This study tried to see mudharabah practices by Islamic banks, whether the implementation and practice mudharabah is in accordance with Islamic Shari'a. In this study also described the practice of gift-giving in early when customers deposit funds in Islamic banks. Practices carried out by the Islamic Bank raises a lot of criticism from people who think that Islamic banks are notdifferent from conventional banks, only the title that sharia. The study was conducted with descriptive methods, compare theory derived from the study ofliterature with the practice in the field. The study found there are many Islamic banking practices in the implementation of mudharabah, particularly in terms ofcapital ownership status and responsibility to bear the risk violate what isoutlined in the Shariah. In terms of gift-giving at the beginning, it was found thatthe gift made Islamic banks with a specific purpose, grant can not be justified inShari’a.